STRATEGI BUDIDAYA TALAS BENENG (Xanthosoma undipes) (STUDI KASUS USAHATANI BAPAK LUKMAN DI DESA PADANG LANGGIS KECAMATAN SERUWAY KABUPATEN ACEH TAMIANG) - Sri Maulina; Rozalina Rozalina; Supristiwendiz Supristiwendiz (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study is to find out the strengths, weaknesses, opportunities and threats as well as to find out the strategies that must be carried out in the cultivation of taro beneng (Xanthosoma undipes) in the farming business of Mr. Lukman, Padang Langgis Village, Seruway District, Aceh Tamiang Regency. The location of the study was determined purposively (intentionally). Sample determination using purposive sampling technique. The data used in compiling the research are primary data and secondary data. The analysis method used in this study is SWOT analysis (Strenghts, Weakness, Opportunities, Threaths). The results of the inventory of internal and external strategic factors of taro beneng cultivation in Mr. Lukman's farming business were obtained results; the biggest strength is that the harvest can be planned, the heaviest weakness is the length of the harvest period, the highest chance is that taro leaves can be used as tea and the heaviest threat is the fluctuating price of taro beneng. The priority of the taro beneng cultivation strategy in Mr. Lukman's farming business from the results of the analysis using the QSPM matrix against four alternative strategies that have been obtained at the matching stage, namely; Adding to the market information, choosing the most efficient marketing channel to avoid losses due to price fluctuations.